2013
DOI: 10.4137/aui.s10746
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Investigation of School-Related Issues Affecting Individuals Diagnosed with Autism Spectrum Disorder and Co-occurring Anxiety and/or Depression

Abstract: This qualitative study investigated the experiences of adolescents and young adults (16 to 21 years old) diagnosed with an autism spectrum disorder (ASD) and co-occurring depression and/or anxiety disorders. The study was conducted with 9 parents of individuals with ASD and 4 individuals diagnosed with ASD and co-occurring anxiety and/or depression. The study used openended, online and face-to-face interviews and yielded rich data associated with a number of broad categories. This paper focuses on associated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(54 citation statements)
references
References 32 publications
6
46
0
1
Order By: Relevance
“…Parents have also reported that their children experienced reduced self-esteem and social skills , mental health difficulties Cappadocia et al, 2012;Penney, 2013), and suicidal feelings and self-harming behaviour . These findings are concerning as quantitative studies of the mental health of young people with ASD indicate that young people with ASD already experience a significantly greater incidence of mental health difficulties than their typically developing peers (Gurney, McPheeters, & Davis, 2006;Hebron & Humphrey, 2012;Kim Szatmari, Bryson, Streiner & Wilson, 2000) and students with other special needs (Hebron & Humphrey, 2012).…”
Section: Themes Of the Broader Literature On Students With Asd In Maimentioning
confidence: 99%
See 4 more Smart Citations
“…Parents have also reported that their children experienced reduced self-esteem and social skills , mental health difficulties Cappadocia et al, 2012;Penney, 2013), and suicidal feelings and self-harming behaviour . These findings are concerning as quantitative studies of the mental health of young people with ASD indicate that young people with ASD already experience a significantly greater incidence of mental health difficulties than their typically developing peers (Gurney, McPheeters, & Davis, 2006;Hebron & Humphrey, 2012;Kim Szatmari, Bryson, Streiner & Wilson, 2000) and students with other special needs (Hebron & Humphrey, 2012).…”
Section: Themes Of the Broader Literature On Students With Asd In Maimentioning
confidence: 99%
“…The body of research on students with ASD in mainstream schools is diverse in terms of country of origin, the focus and the methodologies used. The majority of the literature originated from northern Europe, particularly the United Kingdom (Barnard et al, 2000;Batten et al, 2006;Connor, 2000;Parsons, Lewis & Ellins, 2009;Reid, 2011;Renty & Roeyers, 2006;Stewart, 2012;Tissot & Evans, 2006;Tobias, 2009;Waddington & Reed, 2006;Watson, 2009;Whitaker, 2007;Wittemeyer et al, 2011) Kasari et al, 1999;Scuitto, Richwine, Mentrikoski & Niedzwiecki, 2012;Stoner et al, 2005;Stoner & Angell, 2006), Canada (Brewin et al, 2008;Penney, 2013;Starr et al, 2001;Starr et al, 2006;Starr & Foy, 2010), Australia (Carrington & Graham, 2001;Hay & Winn, 2005;Lilley, 2012;McDonald, 2010;Saggers et al, 2011), a single study in Singapore (Poon et al, 2012), and Sweden (Falkmer et al, 2012).…”
Section: Scope Of the Reviewmentioning
confidence: 99%
See 3 more Smart Citations